Gender Equality and Social Capital Empowerment of Rural Women - Nuraedah, Nuraedah; Bahri, Syamsul, - (Masyarakat: Jurnal Sosiologi, 2025)
This study explores the role of social capital in empowering rural women, focusing on how social networks, trust, and community norms contribute to gender equality and women's decision-making. Despite the recognition of gender equality as a fundamental right, rural women continue to face structural barriers that limit their access to resources and opportunities. By examining the interaction between social capital and women's empowerment, this research aims to fill the gap in understanding the mechanisms that support women's empowerment in rural areas. The research adopts a qualitative approach, utilizing in-depth interviews with 30 women from various villages in Indonesia, complemented by secondary data from empowerment program reports. Key findings reveal that strong social networks, trust within the community, and supportive relationships are essential for enhancing women's empowerment, enabling them to actively participate in decision-making and community change. This study highlights the importance of integrating social capital into empowerment strategies, ensuring that rural women gain greater access to resources and opportunities, which are crucial for achieving gender equality. The results provide valuable insights for policymakers and practitioners to design more effective empowerment programs tailored to rural communities.